Correction: The effects of nattokinase supplementation on collagen-epinephrine closure time, prothrombin time and activated partial thromboplastin time in nondiabetic and hypercholesterolemic subjects - Yoo, Hye Jin; Kim, Minkyung; Kim, Minjoo; Lee, Ayoung; Jin, Chunmei; Lee, Sung Pyo; Kim, Tae Su; Inoue, Kenichi; Lee, Sang-Hyun; Lee, Jong Ho (Food & function, 2019)
Correction for 'The effects of nattokinase supplementation on collagen-epinephrine closure time, prothrombin time and activated partial thromboplastin time in nondiabetic and hypercholesterolemic subjects' by Hye Jin Yoo et al., Food Funct., 2019, 10, 2888-2893.